Nano twin crystal copper-graphene composite material patch antenna and preparation method thereof
Through graphene doped with nanotwin copper composite material, patch antennas with high frequency band responsiveness and temperature stability were prepared, which solved the problem of degradation in performance of traditional antennas at high temperatures and improved their conductivity and mechanical properties.
Patent Information
- Application Number
- CN202411641993.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-18
AI Technical Summary
Existing microstrip patch antennas have poor frequency band responsiveness and stability at high temperatures, and the low flexibility and complex manufacturing processes of metal materials limit their application.
A composite antenna is prepared by pulsed electrodeposition method using a nanotwined copper-graphene composite material doped with graphene and fixed to a dielectric substrate to cover the protective layer to form a patch antenna.
The frequency band responsiveness and stability of nanotwined copper-graphene composite patch antenna at different temperatures is improved, and its conductivity and mechanical properties are enhanced.
Smart Images

Figure CN119627405A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of micro-electromechanical devices, and in particular to a nano-twinned copper-graphene composite patch antenna and a preparation method thereof. Background Art
[0002] Today's world is a world of rapid information development. 5G technology, Internet of Things (IoT) technology and other technologies are booming. Mobile communication devices are increasingly evolving towards wearable and portable directions, which puts higher requirements on flexible, ultra-thin and highly integrated wireless communication components. Fields such as life health monitoring and portable radio frequency tags have already had extremely strong demands for flexible and ultra-thin wireless communication components. How to manufacture wireless communication components that can meet the needs of flexibility and ultra-thinness while ensuring good radiation performance of the components has extremely broad research prospects. There has been very in-depth research in the field of microstrip patch antennas. Traditional high-performance microstrip patch antennas are designed based on traditional high-conductivity metals (such as copper, silver, gold, aluminum, etc.) and have been widely used in fields such as satellite communications, remote sensing detection, and mobile devices.
[0003] Microstrip patch antennas with high shape complexity are often produced by printing and other methods due to their delicate structure. The processing procedures are complicated, a large number of equipment are required, and the manufacturing cost is high. However, for integrated microstrip RF devices or conformal microstrip antennas with high shape complexity, the application of metal materials will be severely limited by their low flexibility and complex manufacturing process. In addition, when microstrip patch antennas are used, the device heats up, resulting in poor frequency band responsiveness and stability of the patch antenna at high temperatures. Summary of the invention
[0004] In view of the deficiencies of the above-mentioned related technologies, the present application provides a nano-twinned copper-graphene composite patch antenna and a preparation method thereof. The present application improves the frequency band responsiveness and stability of the nano-twinned copper-graphene composite patch antenna at different temperatures by using a nano-twinned copper-graphene composite antenna doped with graphene.
[0005] In the first aspect, the present application provides a nano-twinned copper-graphene composite patch antenna using the following technical solution:
[0006] A nano-twinned copper-graphene composite material patch antenna comprises a nano-twinned copper-graphene composite material antenna, a dielectric substrate and a protective layer covering the nano-twinned copper-graphene composite material antenna, wherein the nano-twinned copper-graphene composite material antenna comprises copper and graphene, and the organizational structure of the nano-twinned copper-graphene composite material antenna comprises a twin structure.
[0007] Preferably, in the nano-twinned copper-graphene composite material antenna, graphene is distributed in at least one of a twin boundary region, a grain boundary region and an incoherent twin boundary region.
[0008] Preferably, the twin spacing of the twin structure is 10-500 nm.
[0009] Preferably, the nano-twin copper-graphene composite material antenna has a width of 100-800 μm and a thickness of 1-100 μm.
[0010] Preferably, the dielectric constant of the dielectric substrate is 3-6 and the thickness is 0.5-2 mm.
[0011] Preferably, the dielectric substrate comprises one or more of polyethylene terephthalate, polydimethylsiloxane and epoxy glass fiber composite material. Preferably, considering the economical efficiency, practicality and thermal stability under high frequency, a 1 mm thick polytetrafluoroethylene sheet (with a dielectric constant of 2) is used as the dielectric substrate.
[0012] Preferably, considering economy, practicality and thermal stability at high frequencies, a 1 mm thick polytetrafluoroethylene plate (with a dielectric constant of 2) is used as the dielectric substrate.
[0013] In a second aspect, the present application provides a method for preparing a nano-twinned copper-graphene composite patch antenna using the following technical solution:
[0014] A preparation method of a nano-twinned copper-graphene composite patch antenna, comprising the following steps: placing a copper anode and a cathode plate in an electroplating solution containing copper sulfate and graphene, constructing an electrolyte channel between the cathode plate and the anode, applying a pulse current through the anode and the cathode plate and moving the anode relative to the cathode plate to perform electrodeposition on the cathode plate, thereby obtaining a nano-twinned copper-graphene composite antenna;
[0015] The nano-twinned copper-graphene composite material antenna is removed from the cathode plate, cleaned, and fixed to a dielectric substrate, and then a protective layer covering the antenna is fixed on the dielectric substrate to obtain the nano-twinned copper-graphene composite material patch antenna.
[0016] Preferably, the electroplating solution comprises copper sulfate, polyethylene glycol, graphene and sodium chloride, the concentration of the copper sulfate is 100-150 g / L, the concentration of the polyethylene glycol is 0.03-0.08 g / L, the concentration of the graphene is 0.001-0.15 g / L, and the concentration of the sodium chloride is 50-100 mg / L.
[0017] Preferably, the electroplating solution comprises copper sulfate, polyethylene glycol, graphene and sodium chloride, the concentration of the copper sulfate is 128 g / L, the concentration of the polyethylene glycol is 0.05 g / L, the concentration of the graphene is 0.01 g / L, and the concentration of the sodium chloride is 80 mg / L.
[0018] Preferably, the electroplating solution further comprises 2-mercaptobenzimidazole at a concentration of 0.0003-0.0008 g / L, 1-2-ethylenethiourea at a concentration of 0.0003-0.0008 g / L, and sodium polydisulfide dipropane sulfonate at a concentration of 0.008-0.012 g / L.
[0019] Preferably, the electroplating solution further comprises 2-mercaptobenzimidazole at a concentration of 0.0005 g / L, 1-2-ethylenethiourea at a concentration of 0.0005 g / L, and sodium poly(disulfide)dipropanesulfonate at a concentration of 0.01 g / L.
[0020] Preferably, the electrolyte further comprises an oxidant, wherein the oxidant is 27.5-35 wt % hydrogen peroxide, and the addition amount is 1-10 mL / L.
[0021] Preferably, the pH of the electroplating solution is not greater than 1.
[0022] Preferably, the voltage of the pulse current is 10-50V, and the current density is 300-500mA / cm 2 , the turn-on time is 10-50ms, and the turn-off time is 200-300ms.
[0023] In summary, the present application includes at least one of the following beneficial technical effects:
[0024] 1. The present application improves the frequency band responsiveness and stability of the nano-twinned copper-graphene composite patch antenna at different temperatures by using a nano-twinned copper-graphene composite antenna doped with graphene.
[0025] 2. The present application provides a nano-twinned copper-graphene composite patch antenna whose organizational structure includes a twin structure and forms a graphene-enhanced phase, which is beneficial to further improve the conductivity and mechanical properties of the nano-twinned copper-graphene composite patch antenna.
[0026] 3. The present application prepares a nano-twinned copper-graphene composite material antenna by pulse electrodeposition, and makes the nano-twinned copper-graphene composite material antenna into a nano-twinned copper-graphene composite material patch antenna. Even when doped with graphene, a twin structure is still obtained, and the overall organizational structure is stable and dense, thereby improving the frequency band responsiveness and stability of the nano-twinned copper-graphene composite material patch antenna at different temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a physical picture of the nano-twinned copper-graphene composite material antenna of Example 1 of the present application;
[0028] Figure 2 is a transmission electron microscope image of the nano-twinned copper-graphene composite antenna of Example 1 of the present application;
[0029] Figure 3 is the S of the nano twinned copper-graphene composite patch antenna of Example 1 of the present application 11 Performance graphs;
[0030] Figure 4 The S of the nano twinned copper-graphene composite patch antenna in the 2.7G frequency band of the comparative examples 1-2 and the embodiment 1 of the present application 11 Temperature stability test comparison chart. DETAILED DESCRIPTION
[0031] The present application is further described in detail below in conjunction with examples. The following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. In the following examples, if specific conditions are not specified, they are carried out according to normal conditions or conditions recommended by the manufacturer. The methods used are conventional methods known in the art unless otherwise specified, and the consumables and reagents used are commercially available unless otherwise specified. Unless otherwise specified, the professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the recorded content may also be applied to the present invention.
[0032] The raw materials used in the examples and comparative examples can all be obtained commercially.
[0033] Example 1
[0034] Embodiment 1 of the present application provides a nano-twinned copper-graphene composite patch antenna, and its preparation method is as follows: (1) prepare a basic electroplating solution with a copper sulfate concentration of 128 g / L, a polyethylene glycol concentration of 0.05 g / L, a graphene concentration of 0.1 g / L, a sodium chloride concentration of 80 mg / L, a 2-mercaptobenzimidazole concentration of 0.0005 g / L, a 1-2-ethylenethiourea concentration of 0.0005 g / L and a sodium polydisulfide dipropane sulfonate concentration of 0.01 g / L, adjust the pH to 1 with sulfuric acid, and use a 120 W power ultrasonic wave with a frequency of 40 kHz to uniformly disperse the graphene to obtain an electroplating solution and add it to a plating tank.
[0035] (2) Use copper metal as the anode and stainless steel plate as the cathode plate. Install the anode in a nozzle filled with electroplating solution, and install the cathode plate in a plating tank. Use the nozzle to control the electroplating solution in the nozzle to flow into the plating tank. Build an electrolyte channel between the cathode plate and the anode. Apply pulse current through the anode and cathode plates. The voltage of the pulse current is 40V and the current density is 400mA / cm 2 , the on time is 10ms, the off time is 40ms, and the anode is moved in a serpentine shape relative to the cathode plate to perform electrodeposition on the cathode plate, and a serpentine-shaped nano-twin copper-graphene composite antenna with a thickness of 30μm and a width of 500μm is obtained, such as Figure 1 As shown;
[0036] (3) The nano-twinned copper-graphene composite material antenna is removed from the cathode plate and rinsed with alcohol and water, then pasted to one side of the dielectric substrate and a ground layer is pasted on the other side, the nano-twinned copper-graphene composite material antenna is covered with polyimide tape and pasted to the dielectric substrate to form a protective layer, thereby obtaining the nano-twinned copper-graphene composite material patch antenna (marked as Gr-ntCu), and the nano-twinned copper-graphene composite material patch antenna is connected to the antenna terminal by conductive glue or welding when in use.
[0037] Comparative Example 1
[0038] Comparative Example 1 provides a patch antenna, and its preparation method is as follows: (1) prepare a basic electroplating solution with a copper sulfate concentration of 128 g / L, a polyethylene glycol concentration of 0.05 g / L, a graphene concentration of 0.1 g / L, a sodium chloride concentration of 80 mg / L, a 2-mercaptobenzimidazole concentration of 0.0005 g / L, a 1-2-ethylenethiourea concentration of 0.0005 g / L and a sodium polydisulfide dipropane sulfonate concentration of 0.01 g / L, adjust the pH to 1 with sulfuric acid, and use a 120 W power ultrasonic wave with a frequency of 40 kHz to uniformly disperse the graphene to obtain an electroplating solution and add it to a plating tank.
[0039] (2) Use copper metal as the anode and stainless steel plate as the cathode plate. Install the anode in a nozzle filled with electroplating solution, and install the cathode plate in a plating tank. Use the nozzle to control the electroplating solution in the nozzle to flow into the plating tank. Build an electrolyte channel between the cathode plate and the anode. Apply a DC voltage of 10V and a current density of 50mA / cm2 through the anode and cathode plates. 2 , and the anode is moved in a serpentine shape relative to the cathode plate to perform electrodeposition on the cathode plate, thereby obtaining a serpentine composite patch antenna with a thickness of 30 μm and a width of 500 μm, such as Figure 1 As shown;
[0040] (3) The nano-twinned copper-graphene composite material antenna is removed from the cathode plate and rinsed with alcohol and water, then pasted to one side of the dielectric substrate and a ground layer is pasted on the other side, the nano-twinned copper-graphene composite material antenna is covered with polyimide tape and pasted to the dielectric substrate to form a protective layer, thereby obtaining the nano-twinned copper-graphene composite material patch antenna (marked as DC-Cu), and the nano-twinned copper-graphene composite material patch antenna is connected to the antenna terminal by conductive glue or welding when in use.
[0041] Comparative Example 2
[0042] Comparative Example 2 provides a patch antenna, and its preparation method is as follows: a coarse-grained copper wire is used and pressed into shape by a mold to prepare a pure coarse-grained copper antenna with the same shape as Example 1, and step (3) of Example 1 is used to prepare a coarse-grained copper patch antenna (marked as coarse).
[0043] Test and Inspection
[0044] (1) The nano-twinned copper-graphene composite antenna of Example 1 was imaged by transmission electron microscopy, as shown in FIG. Figure 2 shown.
[0045] (2) Determine the S11 performance diagram of the nano-twinned copper-graphene composite patch antenna of Example 1, as shown in FIG. Figure 3 As shown, the horizontal axis represents the signal frequency band and the vertical axis represents the frequency band loss.
[0046] (3) The nano-twinned copper-graphene composite patch antennas of Examples 1-2 and Example 1 were subjected to S 11 Temperature stability test, get S 11 Temperature stability comparison chart Figure 4 shown.
[0047] Results Analysis
[0048] The following combination Figure 1-4 The experimental results provided are used to explain this application in detail.
[0049] Reference Figure 1 The width of the nano-twinned copper-graphene composite material antenna in Example 1 is about 700 μm, and the width is uniform, the outline is clear, and the size is accurate, indicating that the present application prepares the nano-twinned copper-graphene composite material patch antenna by configuring the electroplating solution and adopting the electrodeposition method, which is beneficial to improving the molding effect and dimensional accuracy of the nano-twinned copper-graphene composite material antenna with a micron-level structure.
[0050] Reference Figure 2It can be seen that the nano-twinned copper-graphene composite material patch antenna in Example 1 of the present application has a high-density twin structure in its organizational structure, and its twin spacing is: 50-100nm, and the graphene is densely distributed inside the grains and at the grain boundaries. The overall organizational structure is stable and dense, and there are no common thermal processing defects such as pores. This shows that the preparation method of the nano-twinned copper-graphene composite material patch antenna of the present application can successfully prepare a nano-twinned copper-graphene composite material antenna doped with graphene and containing a twin structure.
[0051] Reference Figure 3 It can be seen that the minimum frequency band loss of the nano-twin copper-graphene composite patch antenna of Example 1 of the present application corresponds to 3.0 GHz, that is, the nano-twin copper-graphene composite patch antenna of Example 2 of the present application has a good frequency band response in the 3.0 GHz frequency band. Figure 4 It can be seen that the nano-twinned copper-graphene composite material patch antenna of Example 1 has good temperature stability compared to the patch antennas of Comparative Examples 1-2, has good frequency band response and stability at different temperatures, and has smaller signal loss at room temperature, indicating that the nano-twinned copper-graphene composite material patch antenna of Example 1 has good frequency band responsiveness and stability at different temperatures.
[0052] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A nano-twinned copper-graphene composite patch antenna, characterized in that: The invention comprises a nano twinned copper-graphene composite material antenna, a dielectric substrate and a protective layer covering the nano twinned copper-graphene composite material antenna. The nano twinned copper-graphene composite material antenna comprises copper and graphene. The organizational structure of the nano twinned copper-graphene composite material antenna comprises a twinned structure.
2. The nano-twinned copper-graphene composite patch antenna according to claim 1, characterized in that: In the nano-twinned copper-graphene composite material antenna, graphene is distributed in at least one region of a twin boundary region, a grain boundary region, and an incoherent twin boundary region.
3. The nano-twinned copper-graphene composite patch antenna according to claim 1, characterized in that: The twin spacing of the twin structure is 10-500nm.
4. The nano-twinned copper-graphene composite patch antenna according to claim 1, characterized in that: The nano-twin copper-graphene composite material antenna has a width of 100-800 μm and a thickness of 1-100 μm.
5. The nano-twinned copper-graphene composite patch antenna according to claim 1, characterized in that: The dielectric constant of the dielectric substrate is 2-6 and the thickness is 0.5-2 mm.
6. The nano-twinned copper-graphene composite patch antenna according to claim 5, characterized in that: The dielectric substrate includes one or more of polyethylene terephthalate, polydimethylsiloxane and epoxy glass fiber composite material.
7. A method for preparing a nano-twinned copper-graphene composite patch antenna as claimed in claims 1-6, characterized in that: The following steps are involved: The copper anode and cathode plate are placed in an electroplating solution containing copper sulfate and graphene, an electrolyte channel is constructed between the cathode plate and the anode, a pulse current is applied through the anode and cathode plate, and the anode is moved relative to the cathode plate to perform electrodeposition on the cathode plate, thereby obtaining a nano-twinned copper-graphene composite antenna; The nano-twinned copper-graphene composite material antenna is removed from the cathode plate, cleaned, and fixed to a dielectric substrate, and then a protective layer covering the antenna is fixed on the dielectric substrate to obtain the nano-twinned copper-graphene composite material patch antenna.
8. The method for preparing a nano-twinned copper-graphene composite patch antenna according to claim 7, characterized in that: The electroplating solution comprises copper sulfate, polyethylene glycol, graphene and sodium chloride, wherein the concentration of the copper sulfate is 100-150 g / L, the concentration of the polyethylene glycol is 0.03-0.08 g / L, the concentration of the graphene is 0.001-0.15 g / L, and the concentration of the sodium chloride is 50-100 mg / L.
9. The method for preparing a nano-twinned copper-graphene composite patch antenna according to claim 7, characterized in that: The electroplating solution also includes 2-mercaptobenzimidazole with a concentration of 0.0003-0.0008 g / L, 1-2-ethylenethiourea with a concentration of 0.0003-0.0008 g / L, and sodium polydisulfide dipropane sulfonate with a concentration of 0.008-0.012 g / L.
10. The method for preparing a nano-twinned copper-graphene composite patch antenna according to claim 7, characterized in that: The voltage of the pulse current is 10-50V, and the current density is 300-500mA / cm 2 , the turn-on time is 10-50ms, and the turn-off time is 200-300ms.
Citation Information
Patent Citations
Directional-growing nano-twin copper through hole filling method and application thereof
CN106298634A
Nanotwin copper components
CN112941586A
Preparation method of graphene-nano twin copper composite material
CN116427000A
Nanotwin copper components
US20210159477A1